A study of on-line information retrieval systems and their application in the Philippines - Santos, Alicia V.; Neelameghan,A. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1981)
This special problem aims to make a preliminary identification of on-line information retrieval systems in the Philippines, to briefly describe the data access and handling practices of the on-line systems and to contribute to a compilation of information on on-line systems in the hope that it will promote better utilization of available computer hardware and software especially in library applications and better cooperation and resource-sharing among the institutions in the Philippines.
The data for this study were gathered by means of a descriptive survey method making use of questionnaire and interviews. The questionnaires were personally presented to the key personnel involved in the development, implementation, and maintenance of the on-line information retrieval system of the sixteen institutions studied. The key persons in each of these institutions were also interviewed.
The data gathered were then analyzed to prepare brief descriptions of the institutions and the respective on-line information systems developed. These were indexed by name of system, topic areas covered, etc. to facilitate the location of information about the systems in the study.
In the presentation of the on-line information systems, the systems are categorized into two main types - the Bibliographic Information Systems and the Management Information Systems.
Under bibliographic information systems, the arrangement is alphabetical by name of system, while under management information systems, the systems are further classified into areas of application, such as banks and banking, insurance, inventory control, traffic control, water resources management, and other application areas.
This study reveals that in the government sector there is a growing awareness of the many uses of computers in their day to day activities.
In the 60's computer applications being developed and maintained in the government sector are still predominantly clerical data processing (payroll, personnel information, financial accounting, inventory control and others) and paperwork automation. Today, however, the computer's role in the government sector is being widened to cover monitoring of development projects, settlement planning, traffic control management, water resources management, grade management and library and documentation activities.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Information storage and retrieval systems -- Philippines